DHL Express (Italy) v. Commission: Getting It Right Beats Being First - Cristina Volpin (European Papers, 2016)
(Series Information) European Papers - A Journal on Law and Integration, 2016 1(2), 765-768 | European Forum Highlight of 25 July 2016 | (Abstract) In the lack of a harmonised system of leniency at the EU level, the principle of autonomy of national leniency programmes may give rise to serious disparities. Namely, disparities arise in the treatment of firms submitting both a leniency application for immunity with the Commission and a summary application to an NCA for the same cartel, if there are discrepancies in the description of the anticompetitive practice submitted to the two authorities. This Highlight analyses the DHL Express (Italy) v Commission judgment of the Court of Justice, according to which there is no hierarchy nor any legal link between the two leniency applications. It is contended that the ruling of the Court reflects a proper objective of leniency programmes: encouraging the race for leniency that is crucial to their effectiveness.